Macronutrient Intake and Cataract Incidence Among Koreans Aged 60 and Older: A Cross-Sectional Study Using 2015-2017 Korea National Health and Nutrition Examination Survey Data - Jiyoung Choi; Eunju Park (Clinical nutrition research, 2025)
Cataracts are a major cause of vision impairment in older adults and pose a growing concern in aging societies. This study examined the association between dietary macronutrient intake and the odds of having cataracts among 1,619 Korean adults aged ≥ 60 years using data from the 2015-2017 Korea National Health and Nutrition Examination Survey. Cataracts were present in 51.8% of participants. Dietary intake was assessed via 24-hour recall and macronutrient intake was categorized by quartiles and energy ratios. After adjusting for covariates, individuals in the highest quartile of carbohydrate-to-energy intake (> 80%) had 41% higher odds of having cataracts (odds ratio [OR], 1.41; 95% confidence interval [CI], 0.99-2.01), with a significant trend (p for trend = 0.022). In contrast, the highest quartile of protein intake (Q3: 12%-15% energy) was associated with significantly lower odds of having cataracts in women (OR, 0.59; 95% CI, 0.40-0.88). Likewise, fat intake exceeding 18% of total energy was associated with reduced odds of having cataracts (OR, 0.69; 95% CI, 0.49-0.97). Saturated and monounsaturated fat intake also showed inverse associations with the odds of having cataracts. These results suggest that excessive carbohydrate intake, particularly when replacing fats and proteins, may increase the odds of having cataracts in older adults, especially among women. Dietary adjustments aimed at reducing the proportion of carbohydrates and increasing high-quality protein and fat intake may help prevent cataracts in aging populations. Further longitudinal studies are needed to clarify causal relationships and to inform nutritional guideline development.